Comparison of Intravenous Ephedrine Administration of 5 mg and 10 mg Doses on Post Spinal Anesthesia Hypotension in Caesarean Section at Dr. Kariadi General Hospital Semarang - Husein Alaydrus; Amar Rayhan; Johan Arifin; Hari Hendriarto Satoto (Faculty of Medicine, Diponegoro University, 2025)
Background: Hypotension after spinal anesthesia or combined epidural anesthesia in caesarean section (CS) causes adverse effects on the mother and fetus/neonatal. Hypotension often occurs therefore vasopressors could be used routinely and should be used as prophylaxisMethods: Simple randomized controlled trial study of 52 patients undergoing CS at RSUP dr. Kariadi Semarang. Subjects revealed two groups, namely intravenous ephedrine at a dose of 5 mg and a dose of 10 mg. Hemodynamic variables were measured every 3 minutes until the operation was completed.Results: In the comparison of mean arterial pressure (MAP) between the ephedrine 5 mg and ephedrine 10 mg groups, a statistically significant difference was obtained at 30 minutes (P < 0.05) while in the measurement of heart rate (HR) between the ephedrine 5 group mg and ephedrine 10 mg, a statistically significant difference was obtained from 3 to 15 minutes. Hypotension was obtained in 1 patient in the ephedrine 10 mg group and 3 patients in the ephedrine 5 mg group.Conclusion: 10 mg intravenous ephedrine as a prophylactic agent after spinal anesthesia for patients undergoing CS has better hemodynamic outcomes and complications than 5 mg intravenous ephedrine. Keywords: spinal anesthesia, ephedrine, SC, hypotension